1974
DOI: 10.1002/jsfa.2740250803
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritive changes in herring meal during storage at different temperatures with and without antioxidant treatment

Abstract: Herring meals prepared with and without the addition of 0.025 % of 1,Zdihydro-6-ethoxy-2,2,4-trimethylquinoline (EQ) were stored for ten months at -20 "C and 21 "C. Storage changes in the biologically determined energy and protein values of the meals were monitored and related to changes in the chemical characteristics of the meal. Antioxidant treatment stabilised the meal lipid against oxidative changes resulting in loss of solubility, decline in iodine value and formation of peroxides and malonaldehyde. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The rate that spoilage occurs depends on product composition, particularly lipid composition in regards to chain length and hydrogen saturation, as well as environmental factors such as temperature, moisture, surface area, and light (Belitz et al 2004;Sewald and DeVries 2012). Given that lipids present in fish meals contain a high proportion of unsaturated fatty acids and large surface area, they are particularly susceptible to spoilage (El-Lakany and March 1974). Silver Carp also have higher lipid content than Bighead Carp, which may make them more susceptible to spoilage.…”
Section: Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate that spoilage occurs depends on product composition, particularly lipid composition in regards to chain length and hydrogen saturation, as well as environmental factors such as temperature, moisture, surface area, and light (Belitz et al 2004;Sewald and DeVries 2012). Given that lipids present in fish meals contain a high proportion of unsaturated fatty acids and large surface area, they are particularly susceptible to spoilage (El-Lakany and March 1974). Silver Carp also have higher lipid content than Bighead Carp, which may make them more susceptible to spoilage.…”
Section: Compositionmentioning
confidence: 99%
“…The nutritional composition and associated value of traditional reduction fisheries (i.e., fisheries that process their catch into fish meal or fish oil) landings are known to vary by species as well as harvest location and season (Bragadóttir et al 2004;Boran et al 2008). Furthermore, fish meal is more susceptible to oxidative spoilage than other protein meals due to its high surface-areato-volume ratio and higher concentrations of unsaturated fatty acids (El-Lakany and March 1974;Boran et al 2008). Therefore, the variability in nutritional value and protection against oxidation are critical factors in determining the market value of Asian carp meal as a feedstuff as well as its potential to facilitate the control of Asian carp populations and to support the aquafeed industry.…”
mentioning
confidence: 99%
“…Cowey et al . (1984), for example, reported poor growth and efficiency of feed conversion in rainbow trout (Saimo gairdrzerd) fed diets containing mildly oxidized marine lipid without antioxidant protection, whereas Hung et d. (1980,1981) found no significant adverse effect of oxidized dietary lipid in trout even though the concentrations of m3 fatty acids were muck reduced as a result of lipid oxidation.…”
mentioning
confidence: 94%
“…Beisel (198%), in a review of the effects of individual nutrients on immunity, concluded that intake of a-tocopherol in moderate excess of the recommended intake often increases the immune response in animals of a number of species. Blazer and Woke (1984) reported that rainbow trout, fed a vitamin E deficient diet but showing no signs of vitamin E deficiency, nevertheless exhibited poor humoural md cellular immune responses. In a review of vitamin E and immune regulation, Cowin md Gordon (1982) suggested that recommended daily intakes of vitamin E may not be adequate for full imunocomptence…”
mentioning
confidence: 99%
See 1 more Smart Citation